Reliable measurements of brain atrophy in individual patients with multiple sclerosis - Smeets, Dirk; Ribbens, Annemie; Sima, Diana M; Cambron, Melissa; Horakova, Dana; Jain, Saurabh; Maertens, Anke; Van Vlierberghe, Eline; Terzopoulos, Vasilis; Van Binst, Anne-Marie; Vaneckova, Manuela; Krasensky, Jan; et al. (Brain and behavior, 2016)
INTRODUCTION: As neurodegeneration is recognized as a major contributor to disability in multiple sclerosis (MS), brain atrophy quantification could have a high added value in clinical practice to assess treatment efficacy and disease progression, provided that it has a sufficiently low measurement error to draw meaningful conclusions for an individual patient. METHOD: In this paper, we present an automated longitudinal method based on Jacobian integration for measuring whole-brain and gray matter atrophy based on anatomical magnetic resonance images (MRI), named MSmetrix. MSmetrix is specifically designed to measure atrophy in patients with MS, by including iterative lesion segmentation and lesion filling based on FLAIR and T1-weighted MRI scans. RESULTS: MS metrix is compared with SIENA with respect to test-retest error and consistency, resulting in an average test-retest error on an MS data set of 0.13% (MS metrix) and 0.17% (SIENA) and a consistency error of 0.07% (MS metrix) and 0.05% (SIENA). On a healthy subject data set including physiological variability the test-retest is 0.19% (MS metrix) and 0.31% (SIENA). CONCLUSION: Therefore, we can conclude that MSmetrix could be of added value in clinical practice for the follow-up of treatment and disease progression in MS patients.
Keywords: brain atrophy; multiple sclerosis; MSmetrix; magnetic resonance images